(untitled) (Nordic Journal of African Studies, 2000)
The naming of literatures has been traditionally reposed in the geo-cultural analogy. In consequence, we talk of established categories like German literature or Chinese literature as geo-culturally bound national literatures. But with the emergence of new literatures and new literary theories focussing on writings that evolved in former colonies, other ways of naming literatures are nowadays in use. These new ways defy compartmentalization, evade definition, and by corollary are not easily accessible to non-initiates (Ghosh-Schellhorn 1993: 37).